Chlorophyll loss associated with heat-induced senescence in bentgrass. (August 2016) - Jespersen, David; Zhang, Jing; Huang, Bingru
Highlights: Chlorophyll synthesis and degradation pathways were measured to determine mechanisms for chlorophyll loss during heat induced leaf senescence. Chlorophyll loss may be due to increased chlorophyll degradation, particularly associated with enhanced pheophytinase (PPH) activity. The analysis of an Arabidopsis pph mutant further demonstrated that PPH could play key roles in heat-accelerated chlorophyll degradation. Abstract: Heat stress-induced leaf senescence is characterized by the loss of chlorophyll from leaf tissues. The objectives of this study were to examine genetic variations in the level of heat-induced leaf senescence in hybrids of colonial ( Agrostis capillaris)  × creeping bentgrass ( A grostis stolonifera) contrasting in heat tolerance, and determine whether loss of leaf chlorophyll during heat-induced leaf senescence was due to suppressed chlorophyll synthesis and/or accelerated chlorophyll degradation in the cool-season perennial grass species. Plants of two hybrid backcross genotypes ('ColxCB169' and 'ColxCB190') were exposed to heat stress (38/33 °C, day/night) for 28 d in growth chambers. The analysis of turf quality, membrane stability, photochemical efficiency, and chlorophyll content demonstrated significant variations in the level of leaf senescence induced by heat stress between the two genotypes, with ColXCB169 exhibiting a lesser degree of decline in chlorophyll content, photochemical efficiency and membrane stability than ColXCB190. The assays of enzymatic activity or gene expression of several major chlorophyll-synthesizing (porphobilinogen deaminase, Mg-chelatase, protochlorophyllide-reductase) and chlorophyll-degrading enzymes (chlorophyllase, pheophytinase, and chlorophyll-degrading peroxidase) indicated heat-induced decline in leaf chlorophyll content was mainly due to accelerated chlorophyll degradation, as manifested by increased gene expression levels of chlorophyllase and pheophytinase, and the activity of pheophytinase (PPH), while chlorophyll-synthesizing genes and enzymatic activities were not differentially altered by heat stress in the two genotypes. The analysis of heat-induced leaf senescence of pph mutants of Arabidopsis further confirmed that PPH could be one enzymes that plays key roles in regulating heat-accelerated chlorophyll degradation. Further research on enzymes responsible in part for the loss of chlorophyll during heat-induced senescence could aid in the development of genotypes with stay-green traits either through marker assisted selection or transgenic approaches.